2016
DOI: 10.3390/rs8100834
|View full text |Cite
|
Sign up to set email alerts
|

Flash Flood Monitoring with an Inclined Lidar Installed at a River Bank: Proof of Concept

Abstract: Flash floods need to be monitored from a safe place, ideally with noncontact instruments installed at a riverbank and oriented so that they look obliquely at the water surface. The “inclined Lidar” technique could be useful for this purpose. It works based on the fact that a near-infrared Lidar mounted with a large incidence angle can detect suspended particles slightly below the surface, provided that the water is very turbid, something which is likely during flash floods. To check this hypothesis, an inexpen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…However, this layer is unlikely to exist since: (1) as far as we know, in practice a near-infrared and low-power Lidar cannot detect suspended particles below a depth of a few decimeters (see Section 2.3); (2) three water column characterizations performed at Valsequillo at different times (November 2014 and April and June 2015; see triangles at Figure A1b) with a multi-parameter probe ("Exo2", Ysi, Yellow Springs, OH, USA) did not show any obvious stratification at a depth of ≈ 1.7 m (in terms of water temperature, oxygen demand, turbidity and chlorophyll-a concentration), and above all, (3) the same feature was observed later with the test Lidar pointing at a turbid river (the Amacuzac River [27]) when the stage was less than 1.0 metre. Therefore, the Lidar data suggesting the apparent detection of a layer below the water surface were likely to be due to a failure of the test Lidar under low signal strength conditions.…”
Section: Appendix B-small Daily Oscillations Of the Lidar Data Associmentioning
confidence: 71%
See 1 more Smart Citation
“…However, this layer is unlikely to exist since: (1) as far as we know, in practice a near-infrared and low-power Lidar cannot detect suspended particles below a depth of a few decimeters (see Section 2.3); (2) three water column characterizations performed at Valsequillo at different times (November 2014 and April and June 2015; see triangles at Figure A1b) with a multi-parameter probe ("Exo2", Ysi, Yellow Springs, OH, USA) did not show any obvious stratification at a depth of ≈ 1.7 m (in terms of water temperature, oxygen demand, turbidity and chlorophyll-a concentration), and above all, (3) the same feature was observed later with the test Lidar pointing at a turbid river (the Amacuzac River [27]) when the stage was less than 1.0 metre. Therefore, the Lidar data suggesting the apparent detection of a layer below the water surface were likely to be due to a failure of the test Lidar under low signal strength conditions.…”
Section: Appendix B-small Daily Oscillations Of the Lidar Data Associmentioning
confidence: 71%
“…The proposed technique could also be used to monitor flash floods in rivers: as a matter of fact, the water is usually very turbid during this type of flood [4,27]; in this case, it is worth noting that "glint noise" should only slightly affect the response of a common Lidar pointing at a water surface with an incidence angle between ≈ 30 • and 70 • , unless the surface agitation is extreme [2,9].…”
Section: Other Potential Applications Of the Proposed Techniquementioning
confidence: 99%
“…The typical height of the scanner above the mean water level prior to the passage of the tidal bore was 8 m. A recent description of the working principle of the LiDAR can be found in [10]. A description of the 2D scanner used in the present study is provided in [9].…”
Section: Field Experiments Descriptionmentioning
confidence: 99%
“…In contrast to other remote sensing tools (e.g., RaDAR, video camera), 2D scanners are capable of accurately measuring surf zone wave geometry. In freshwater conditions where the presence of foam or air bubbles (required to scatter the incident laser) is scarcer, single point LiDAR has applications for steady water body monitoring [10] as well as for more dynamical systems such as flash floods [11]. In laboratory conditions, Martins, K. et al [12] demonstrated the potential of 2D LiDAR to describe the geometry of breaking waves at prototype scale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation